Cryptic pregnancy or negation of the pregnancy: an unknown reality - Llorca-Porcar, Alicia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Cryptic pregnancy or denial of pregnancy, according to research, presents alterations that generate risk of death and/or maternal and infant disease. Part of society seems to be unaware or denies the existence of this disease. The objectives of this investigation are the search, collection and dissemination of existing information to detect a possible reality that can be acted upon. The results show the existence of this reality, together with maternal helplessness, lack of support and punishment, rather than help. Little research and dissemination of the problem and the need to detect and help these women and their offspring is evident.